The Integration and Development of Guangdong Folk Music in Contemporary Chinese Music Composition - Miao, Yeshu (Pacific International Journal, 2024)
This study explores the integration and development of Guangdong folk music in contemporary Chinese music composition. With the rapid modernization of Chinese society, traditional folk music has faced challenges and opportunities for preservation and transformation. Focusing on Guangdong province, renowned for its rich folk music heritage, this research investigates how Guangdong folk music has influenced and merged with contemporary music composition. The study includes interviews with music teachers and students at Zhaoqing University, providing insights into the perspectives of the younger generation of musicians and educators regarding the fusion of traditional and modern music elements. By analyzing case studies and discussing the challenges and potential of integrating folk music into contemporary compositions, the study aims to contribute to a deeper understanding of how regional music traditions can be preserved and revitalized in the context of modern creative practices. The findings highlight the importance of music education and cultural preservation in ensuring the continued relevance of Guangdong folk music in the 21st century.